2022
DOI: 10.53550/eec.2022.v28i01s.018
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Docking; future of Medicinal Research

Abstract: Molecular docking is a Molecular modelling technique that is used to predict the interaction between two molecules such as drugs, enzymes or proteins. It predicts the structure of the interacting molecules using computational modelling. The objective is to obtain plausible three-dimensional structures of the molecules under study. The candidates produced by docking are ranked by various methods to identify the most likely naturally occurring structure. This review encompasses the various types of docking model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
1
0
Order By: Relevance
“…The use and application of computational methods have facilitated the proliferation of biological databases and become an early driving force for developing MD techniques towards drug designing (20). Molecular Docking is the future of medicinal research as reported recently (21).…”
Section: Introductionmentioning
confidence: 99%
“…The use and application of computational methods have facilitated the proliferation of biological databases and become an early driving force for developing MD techniques towards drug designing (20). Molecular Docking is the future of medicinal research as reported recently (21).…”
Section: Introductionmentioning
confidence: 99%
“…Application of machine learning techniques can aid in assessing the potential toxicity of chemicals significantly reducing the time and cost associated with conducting biological experiments. One of the methods used in this study is molecular docking-a computational modeling technique that enables the prediction of the interactions between two molecules such as drugs, enzymes, or proteins [ 40 ]. Molecular docking can be successfully applied for the study of potential ligand (PFAS)-protein binding [ 41 ].…”
Section: Introductionmentioning
confidence: 99%